The Complex Dynamics of Resources and Maintaining Factors in Social Networks for Alcohol-Use Disorders: A Cross-Sectional Study - Braus, Niels; Kewitz, Sonja; Hunger-Schoppe, Christina (Frontiers in Psychology, 2022)
Systemic therapy considers the complex dynamics of relational factors and resources contributing to psychological symptoms. Negative maintaining factors have been well researched for people suffering from Alcohol-use Disorders (AUD). However, we know little about the complex dynamics of these negative factors and resources. We interviewed fifty-five participants suffering or fully remitted from Alcohol-use disorders in this cross-sectional study (M = 52 years; 33% female). The interviews focused on relational factors (e.g. social support and social negativity) referring to a Support Social Network and a Craving Social Network. The Craving Social Network included all significant others who were associated with craving situations. We compared the network characteristics of the group suffering from Alcohol-use Disorders (n=38) to a fully remitted control group (n=17). The abstinent group with full remission named on average fewer individuals in the Craving Social Networks. They had lower social negativity mean scores in the Support Social Network compared to the non-remitted group (d= .74). In the Craving Social Network, the mean scores of social support were significantly higher than the median for both groups (d= 2.50). These findings reveal the complex interplay of relational patterns contributing to the etiology, maintenance, and recovery from Alcohol-use disorders. A successful recovery can be linked to increased social resources and reduced relations associated with craving. However, craving-associated relations represent an important source of social support. Future research should investigate this ambivalence for the systemic perspective on the explanation and treatment of Alcohol-use disorders.